2013
DOI: 10.1631/jzus.b1200159
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of oat bran extracts on human dermal fibroblast injury induced by hydrogen peroxide

Abstract: Abstract:Oat contains different components that possess antioxidant properties; no study to date has addressed the antioxidant effect of the extract of oat bran on the cellular level. Therefore, the present study focuses on the investigation of the protective effect of oat bran extract by enzymatic hydrolysates on human dermal fibroblast injury induced by hydrogen peroxide (H 2 O 2 ). Kjeldahl determination, phenol-sulfuric acid method, and high-performance liquid chromatography (HPLC) analysis indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 19 publications
0
26
1
Order By: Relevance
“…Finally, it can be noted that recently Feng et al 70 demonstrated for the first time the protective effect of oat at the cellular level due to the antioxidant properties of oat bran extract by enzymatic hydrolysates which prevents human dermal fibroblast injury induced by hydrogen peroxide H 2 O 2 . Yet, precautions should be taken as regards for long time cream based Avena sativa application or intolerance of this plant 71 .…”
Section: Proteinsmentioning
confidence: 94%
“…Finally, it can be noted that recently Feng et al 70 demonstrated for the first time the protective effect of oat at the cellular level due to the antioxidant properties of oat bran extract by enzymatic hydrolysates which prevents human dermal fibroblast injury induced by hydrogen peroxide H 2 O 2 . Yet, precautions should be taken as regards for long time cream based Avena sativa application or intolerance of this plant 71 .…”
Section: Proteinsmentioning
confidence: 94%
“…Oat bran is the outer layer of the oat kernel and is mainly a processed byproduct used as poultry feed in the past. Recently, researchers have found that the bran contains 13–20 g/100 g protein, 2–12 g/100 g fat, 60 g/100 g carbohydrates, 11 g/100 g dietary fiber and 10.4 g/100 g β-glucan [ 2 ]. The most important and enthusiastic topic is dietary fiber including both soluble and insoluble dietary fiber [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The soluble fractions of fi bre exhibit a higher antioxidant activity than the insoluble ones (Esposito et al, 2005). It also has a greater gelation capacity and shows emulsifying properties (Sozer et al, 2014;Feng et al, 2013). The amount and fractional composition of dietary fi bre found in cereals depend on the species.…”
Section: Introductionmentioning
confidence: 99%